2020
DOI: 10.1038/s41598-020-74607-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental optimization of the energy for breast-CT with synchrotron radiation

Abstract: Breast Computed Tomography (bCT) is a three-dimensional imaging technique that is raising interest among radiologists as a viable alternative to mammographic planar imaging. In X-rays imaging it would be desirable to maximize the capability of discriminating different tissues, described by the Contrast to Noise Ratio (CNR), while minimizing the dose (i.e. the radiological risk). Both dose and CNR are functions of the X-ray energy. This work aims at experimentally investigating the optimal energy that, at fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…45 Similarly, in PB-CT, an optimum energy can minimize the amount of noise perceived in an image at an acceptable radiation dose. Oliva et al 33 recently concluded that an optimum energy range of 26 to 28 keV produced the highest CNR, complementing the results of Delogu et al, 34 who discovered that the highest quality images were created by 28 keV x-rays. However, these two studies applied a different detector, namely Pixirad-8 photon-counting detector with 60 μm pitch in a honeycomb matrix, from the one used in this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…45 Similarly, in PB-CT, an optimum energy can minimize the amount of noise perceived in an image at an acceptable radiation dose. Oliva et al 33 recently concluded that an optimum energy range of 26 to 28 keV produced the highest CNR, complementing the results of Delogu et al, 34 who discovered that the highest quality images were created by 28 keV x-rays. However, these two studies applied a different detector, namely Pixirad-8 photon-counting detector with 60 μm pitch in a honeycomb matrix, from the one used in this study.…”
Section: Discussionmentioning
confidence: 71%
“…32 There is limited research specifically underlining the most suitable x-ray energy for PB-CT, and the work that has been done has produced varying results. Recent studies by Oliva et al 33 and Delogu et al 34 discovered an optimum energy range between 26 and 28 keV for an ideal detector. Some studies claim that energies of around 32 to 35 keV are most appropriate, 30,31 but these studies have not examined x-ray energies lower than 32 keV.…”
Section: Introductionmentioning
confidence: 99%
“…A full volume acquisition is obtained via subsequent 180-degree scans performed at different vertical positions 42 , each of a duration of 40 seconds or less, resulting in an expected total examination time of 5 to 10 minutes. According to breast dimension and glandularity, the x-ray energy is selected between 25 and 30 keV 43 , with a target mean glandular dose delivery of 5 mGy or less. A detailed description of this breast CT project was recently reported 12 .…”
Section: Iia Synchrotron Radiation Breast Ctmentioning
confidence: 99%
“…Indeed, micro-CT has proven to be useful for virtual dissections, 3D reconstruction and morphological descriptions of the head [ 1 , 2 ], muscles [ 2 , 3 , 4 ], brain [ 5 ], digestive [ 6 , 7 ] and reproductive [ 8 , 9 , 10 , 11 ] systems, as well as insect fossils [ 12 , 13 , 14 , 15 ]. Moreover, Synchrotron radiation X-ray phase-contrast microtomography (SR-PhC micro-CT) allows the use of high-resolution imaging coupled with segmentation, for 3D morphological analyses with high image contrast-to-noise ratios in biological tissues, and does not require the use of contrast agents, even in samples with weak X-ray absorption [ 16 , 17 , 18 , 19 ]. In recent decades, it has been applied as a non-invasive technique to observe external and internal anatomical structures of living insects [ 20 , 21 ], and specimens immersed in ethanol after fixation [ 2 , 6 ] or embedded in amber [ 22 ].…”
Section: Introductionmentioning
confidence: 99%